Cover Picture: Bimetallic Au2Cu6 Nanoclusters: Strong Luminescence Induced by the Aggregation of Copper(I) Complexes with Gold(0) Species (Angew. Chem. Int. Ed. 11/2016). Issue 11 (24th February 2016) - Kang, Xi; Wang, Shuxin; Song, Yongbo; Jin, Shan; Sun, Guodong; Yu, Haizhu; Zhu, Manzhou
Abstract : The Monkey King, a famous Chinese mythical creature with the magic golden cudgel tames and defeats the monsters in the journey to the West. In their Communication onpage 3611 ff., M. Zhu, H. Yu, and co‐workers describe how the aggregation of wild copper complexes with neutral gold species induces strong luminescence by the restriction of intramolecular rotations.